Intermolecular benzoyl group transfer reactivity in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate: controlling reactivity by solvate (pseudopolymorph) formation - Krishnaswamy, Shobhana; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2011)
Racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate (rac-3), which usually crystallizes in a monoclinic lattice (Form I, P2(1)/c) from common organic solvents, when crystallized from 2-propanol yielded concomitantly, thin whisker like crystals (Form II, triclinic, P (1) over bar) with inclusion of 2-propanol and water molecules, along with the Form I crystals. Thin fibre-like crystals were also obtained on crystallization from toluene, with inclusion of toluene and water in the crystal lattice (Form III). The Form II and Form III crystals could be converted into the Form I crystals thermally via melt crystallization. Form I crystals exhibit a facile transesterification reaction, but the solvated crystals are unreactive under the same conditions until their transformation to the reactive form. The reactivity patterns of the Form I and Form II crystals correlate well with the molecular organization in them. Since reactivity of the crystals of rac-3 depends on the solvent and the method of crystallization, and the thermal transition of one crystal form to the other, these phase changes can be used as a switch to control the benzoyl transfer reactivity of the constituent molecules in crystals.

Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis

Intermolecular acyl-transfer reactions in molecular crystals - Shashidhar, Mysore S.; Krishnaswamy, Shobhana (Accounts of Chemical Research, 2019)
CONSPECTUS: It is far more difficult to recognize and predict the chemical reactions that a molecule of an organic compound can undergo in crystalline (solid) state as compared to the solution state (the "organic functional group" approach), since the published data on solid-state structure reactivity investigations and correlations are scant. The discovery of the first intermolecular acyl-transfer reaction in molecular crystals of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (DiBz) during our attempts to develop methods for the synthesis of phosphoinositols, motivated us to find other molecular crystals capable of supporting similar reactions. Small changes to the molecular structure of DiBz yielded analogues with different crystal structures which showed varying degrees of acyl transfer reactivity as compared to the crystals of DiBz. A systematic investigation of the structures, polymorphism, cocrystallization behavior, and the corresponding reactivity of these crystals allowed us to correlate the acyl transfer reactivity with their structures and inherent noncovalent interactions and provided crucial insights into the mechanism of these reactions. Polymorphs or cocrystals of these compounds exhibited dissimilar reactivities due to differences in the molecular conformation and/or arrangements in their crystals. The knowledge of phase transitions between polymorphs enabled us to control and tune the reactivity in the solid state. We could identify three conditions essential for intermolecular acyl transfer: (i) favorable relative geometry of the electrophile (ester C=O) and the nucleophile (OH), (ii) noncovalent interactions (C-H center dot center dot center dot pi) between the reacting molecules which help in maintaining the facility and specificity of the reaction, and (iii) the presence of channels in the lattice which enable propagation of the reaction in the crystal. Based on this supramolecular structure reactivity correlation, we identified other molecular crystals (composed of molecules of widely different molecular structure from that of DiBz) from a survey of the Cambridge Structural Database (CSD) and predicted their acyl transfer reactivity. The increased availability of user-friendly modern X-ray diffractometers and related software has enabled efficient collection, analysis and interpretation of single crystal X-ray diffraction data, essential for such studies. The rapidly expanding CSD facilitates the identification of crystals with similar structures and reactivity patterns. In a wider perspective, facile reactions in molecular crystals fascinate chemists because these reactions usually exhibit unique product selectivity and have the potential to be developed as sustainable green reactions. We are optimistic that similar approaches for the study of other group transfer reactions in molecular crystals would augment and widen the scope of chemical reactions in molecular crystals in particular and the solid state in general. The ability to predict the reactivity of molecules in their crystals could find applications in organic synthesis, material science and industry. Realization of the involvement of inositol derivatives in cellular processes led to the discovery of cellular signal transduction mechanisms. The ability of inositol derivatives to support facile acyl-transfer reactions in the crystalline state might well have opened a new avenue for research in the area of organic solid-state reactions.